2017
DOI: 10.1016/j.ceramint.2016.12.096
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization and catalytic application of Barium molybdate (BaMoO 4 ) and Barium tungstate (BaWO 4 ) in the gas-phase oxidation of toluene

Abstract: Barium molybdate and Barium tungstate are important materials due their photoluminescent properties and they also have catalysis and photocatalysis applications. In this work, powders of these compounds were prepared by microwave-assisted hydrothermal (MAH) method and polymeric precursor method (PPM) and their structural and optical properties were studied. Furthermore, these materials were employed as solid catalysts towards gas phase toluene oxidation reactions. X-ray diffraction confirms the purity of mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 40 publications
0
20
0
1
Order By: Relevance
“…Comparing the results of BET, it could be concluded that specific surface areas had no influence on the catalytic activities presented in this work. The superior performance presented by CuWO4 was attributed to its higher reducibility and oxygen mobility (higher hydrogen consumption, according to H2-TPR measurements) [46]. The hydrogen consumption (Table 3) for…”
Section: Resultsmentioning
confidence: 97%
“…Comparing the results of BET, it could be concluded that specific surface areas had no influence on the catalytic activities presented in this work. The superior performance presented by CuWO4 was attributed to its higher reducibility and oxygen mobility (higher hydrogen consumption, according to H2-TPR measurements) [46]. The hydrogen consumption (Table 3) for…”
Section: Resultsmentioning
confidence: 97%
“…In this paper, CaWO 4 powders were synthesized by microwave-assisted hydrothermal (MAH) method and polymeric precursor method (PPM). PPM allows to obtain high-purity homogeneous systems at the molecular scale due the immobilization of the metal cations in a polymeric networks, which can be annealed at relatively low temperatures (700 ºC) [14][15] . Microwave-assisted hydrothermal method is able to synthesize inorganic materials, such as tungstates, because the high frequency of the electromagnetic radiation promotes a rapid heating accelerating the chemical reactions [16][17][18] .…”
Section: -mentioning
confidence: 99%
“…No significant change is observed in these XANES spectra as a function of the preparation method for CaWO 4 samples. EXAFS spectra at W L III -edge were also measured in order to obtain quantitative information at local structure such as the number, position and identity of atoms surrounding the absorbing element as well as structural disorder within the coordination spheres 14 . Fig.…”
Section: X-ray Absorption Spectroscopy Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Commonly, metal oxides such as titanium dioxide and zinc oxide are used to carry out PCO studies. [15][16][17] For instance, methanol PCO was previously explored in a few studies with metal oxide-based photocatalysts. [18][19][20][21] In contrast to metal oxide-based photocatalysis, a carbonbased catalyst is a metal-free option that is low in cost and uses carbon, which has high abundance in the earth.…”
Section: Introductionmentioning
confidence: 99%